(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Dуnamic ion-exchange properties of silica immobilized with covalent ethyl-sulphonic groups was studied. It was found that this ionexchanger had properties of strong-acid ionexchanger and adsorbed metals by electrostatic mechanism.